1981
DOI: 10.1161/01.atv.1.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of cholesteryl ester synthesis in macrophages by extracts of atherosclerotic human aortas and complexes of albumin/cholesteryl esters.

Abstract: This research was supported by research Grants HL 20948 and NS 09287 from the National Institutes of Health. Dr. Hoff was an Established Investigator of the American Heart Association.Address This sequence of uptake, hydrolysis, and reesterification occurs when macrophages are incubated with LDL that has been rendered polyanionic by chemical derivitization, such as by maleylation 57 or by reaction with malondialdehyde, 7 " 9 in addition to acetylation. 5 ' 9 A similar uptake can be triggered by allowing LDL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Our studies indicate that such a cluster may be provided by the amino acids of bovine plasma albumin. Support for this proposal is derived from earlier studies conducted by Goldstein et al (11). These investigators demonstrated that coacervates of bovine plasma albumin and cholesteryl ester formed by sonication were recognized in part by the scavenger receptor of murine peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our studies indicate that such a cluster may be provided by the amino acids of bovine plasma albumin. Support for this proposal is derived from earlier studies conducted by Goldstein et al (11). These investigators demonstrated that coacervates of bovine plasma albumin and cholesteryl ester formed by sonication were recognized in part by the scavenger receptor of murine peritoneal macrophages.…”
Section: Discussionmentioning
confidence: 90%
“…Several other cholesteryl ester-rich lipoprotein complexes have been identified that bind to the scavenger receptor of macrophages and promote the intracellular accumulation of cholesteryl esters. These include LDL modified by malondialdehyde (6,7), diketene (8), or endothelial cells (9,10); particulate complexes of bovine serum albumin with cholesteryl ester (11); and lipid-protein particles extracted from human atherosclerotic aortas (11).…”
mentioning
confidence: 99%
“…Nonetheless, it is possible that this technique would not be able to discern a subpopulation of particles with a relatively modest enrichment of CE, and so this possibility must still be formally considered. In this regard, it is well documented that CE-rich particles exist in atherosclerotic lesions and can lead to CE accumulation in macrophages (67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…Human atherosclerotic lesions contain lipoproteinlike particles that have been postulated to promote macrophage foam cell formation, 34 and several mechanisms modify LDL to a highly atherogenic lipoprotein in vitro. 1 " 5 -7 -9 - 15 Certain of these pathways may generate particulate lipoprotein.…”
Section: Discussionmentioning
confidence: 99%